2009
DOI: 10.1016/j.jaci.2009.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and leptin receptor expression in asthma

Abstract: Decreased expression of leptin/leptin receptor characterizes severe asthma and is associated with airway remodeling features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
113
1
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(121 citation statements)
references
References 40 publications
2
113
1
5
Order By: Relevance
“…We found evidence of leptin and leptin receptor expression within airway epithelium. Previous reports have also shown that leptin and leptin receptor are expressed in airway epithelium (24), and bronchial expression of leptin is increased in chronic obstructive pulmonary disease (25,26). Leptin seems to be involved in embryonic lung growth and maturation (27,28), and in fibroproliferative responses in the lung to bleomycin (29).…”
Section: Discussionmentioning
confidence: 95%
“…We found evidence of leptin and leptin receptor expression within airway epithelium. Previous reports have also shown that leptin and leptin receptor are expressed in airway epithelium (24), and bronchial expression of leptin is increased in chronic obstructive pulmonary disease (25,26). Leptin seems to be involved in embryonic lung growth and maturation (27,28), and in fibroproliferative responses in the lung to bleomycin (29).…”
Section: Discussionmentioning
confidence: 95%
“…We show that elevated leptin increases the odds of abnormal FEV 1 by more than twofold after adjustment for BMI. A role for this adipocyte-derived cytokine in impaired lung function is plausible because leptin has receptors in the lung and is increased in inflammation (41,47,48). The triglycerides and HDL mechanism underlying the association of leptin with lung function is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Single or repeated injections of glucocorticoids were also shown to elevate rat plasma leptin in a dose-dependent manner [12]. On the other hand, leptin receptor expression was decreased in vitro in human bronchial epithelial cells by transforming growth factor b1 (TGF-b1) [13]. Despite these results, no mechanism of leptin expression has been proposed.…”
mentioning
confidence: 99%